Cultural variations in whether, why, how, and at what cost people are proactive: A followership perspective - Urbach, T.; Den Hartog, D.N.; Fay, D.; Parker, Sharon; Strauss, K. (SAGE PUBLICATIONS INC, 2020)
The objective of this conceptual article is to illustrate how differences in societal culture may affect employees’ proactive work behaviors (PWBs) and to develop a research agenda to guide future research on cross-cultural differences in PWBs. We propose that the societal cultural dimensions of power distance, individualism–collectivism, future orientation, and uncertainty avoidance shape individuals’ implicit followership theories (IFTs). We discuss how these cross-cultural differences in individuals’ IFTs relate to differences in the mean-level of PWB individuals show (whether), in the motivational states driving individuals’ PWBs (why), in the way individuals’ enact PWBs (how), and in the evaluation of PWBs by others (at what cost). We recommend how future research can extend this theorizing and unpack the proposed cross-cultural differences in PWBs, for example, by exploring how culture and other contextual variables interact to affect PWBs.